2023
DOI: 10.1097/jhm-d-22-00007
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers' Perceptions of On-Site Childcare

Abstract: Goal: Measures taken by healthcare organizations to address COVID-19 highlighted the long-standing lack of childcare infrastructure required to support healthcare workers. This study, designed to provide evidence to support operations at an academic medical center, looked at the influence that in-house and emergency childcare could have on the retention, recruitment, and productivity of healthcare workers. This study also outlined the implications that childcare, or its lack, has for healthcare org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Given the association of perceived organizational support with exhaustion and the well-demonstrated negative emotional, financial, and patient care–associated impacts of a burned-out workforce, health care organizations must carefully evaluate their current state and consider mechanisms for improvement. One approach to decreasing caregiving stressors is to ensure the availability of on-site childcare, which is very important to health care workers, particularly for emergency caregiving needs [ 7 ]. Other options include home-based childcare and eldercare services, concierge services and school break camps, and paid parental and sick leave, which can also be used for eldercare responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the association of perceived organizational support with exhaustion and the well-demonstrated negative emotional, financial, and patient care–associated impacts of a burned-out workforce, health care organizations must carefully evaluate their current state and consider mechanisms for improvement. One approach to decreasing caregiving stressors is to ensure the availability of on-site childcare, which is very important to health care workers, particularly for emergency caregiving needs [ 7 ]. Other options include home-based childcare and eldercare services, concierge services and school break camps, and paid parental and sick leave, which can also be used for eldercare responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…With increases in patient volume and the closing of child and adult care facilities, women in the health care field experienced a disproportionate increase in their professional and personal caregiving and reported feeling that there was not enough support for them to care for their families from their organizations [ 2 ]. In a recent study, 49% of health care workers reported that emergency childcare needs disrupted their work, including canceled clinics and surgeries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been supported in American Medical Association policy, and there is great interest in this concept 4,5 . However, still a very small number of hospitals o er these kinds of programs currently in Canada 6 . ere is a lack of supportive studies on the topic of childcare for healthcare providers which would serve to motivate development of initiatives that could impart bene t. Investigations may additionally highlight the impact of the stress that is associated with insucient childcare support, particularly so in Canada.…”
Section: Educationmentioning
confidence: 99%